1969
DOI: 10.1243/jmes_jour_1969_011_017_02
|View full text |Cite
|
Sign up to set email alerts
|

Noise and Flow Characteristics of Coaxial Jets

Abstract: The noise from cold subsonic coaxial jets issuing from concentric nozzles with external mixing has been examined and an attempt made to relate the results to the flow patterns of the jets. As the velocity of the annular jet was increased in relation to a given central jet velocity, an initial attenuation of the jet noise was observed. On further increasing the annular jet velocity until the velocities of the two streams were nearly equal, the noise was in excess of that of the central jet alone. An attempt has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 7 publications
3
23
0
Order By: Relevance
“…The NASA interim method, based on exte lion of the earlier F studies of Olsen and Friedman and Williams, et al 5 has been shown to agree reasonably well with full-J scale static and flight data 6 for low to moderately-high bypass ratio coaxial jets.…”
mentioning
confidence: 71%
“…The NASA interim method, based on exte lion of the earlier F studies of Olsen and Friedman and Williams, et al 5 has been shown to agree reasonably well with full-J scale static and flight data 6 for low to moderately-high bypass ratio coaxial jets.…”
mentioning
confidence: 71%
“…An analytical two-dimensional model on turbulent coaxial jets was proposed by Morton [46], while another model was proposed for a coaxial burning jet by Beer et al [7]. The importance of the velocityratio between the two coaxial jet streams with respect to noise attenuation was first demonstrated by Williams et al [102] and their study was soon followed by those of Champagne and Wygnaski [14], Kwan and Ko [29][30][31] and Ko and Au [28], just to name a few. On the other hand, influences due to other flow parameters of interest, such as the initial turbulent intensity and the wall thickness, were investigated by Matsumoto et al [40].…”
Section: Circular Coaxial Modified Nozzle Jetsmentioning
confidence: 99%
“…There are numerous studies on the coaxial jets discharging into the still air and their unique phenomenon. The works on the vertical structures of the coaxial jets were reported by many researchers (Chigier, 1964;66 S. TORII Williams, 1969;Champange, 1971;Ko, 1985;Rehab, 1997). Kiwata et al (1997) indicated the existence of a recirculating region along the axis of the coaxial jets.…”
Section: Introductionmentioning
confidence: 98%